Специфіка дискурсу медичної реклами - Tsupikova, O. A.; Цупікова, Олена Анатоліївна (Маріуполь : МДУ, 2020)
Статтю присвячено особливостям дискурсу медичної реклами, окреслено специфіку об’єктів рекламування, схарактеризовано функції і мотиви дискурсу реклами медичних препаратів, проаналізовано прийоми впливу на адресата в означеному дискурсі. The article is devoted to the peculiarities of medical advertising discourse, particular features of the advertised objects are outlined, functions and reasons of medications advertising discourse are described, and methods of influencing the addressee in this discourse are analyzed. It is stated that in the modern Ukrainian advertising reality a significant place is occupied by medical goods and services advertising. The relevance and importance of an in-depth study of this discourse are substantiated. The purpose of this article is to analyze the features of medical advertising discourse. Descriptive and functional research methods and a dictionary definition analysis method constitute a research methodology.
Peculiarities of medical advertising discourse
Keywords: рекламний медичний дискурс; мотив; функція; прийоми впливу; medical advertising discourse; reason; function; methods of influence